Aberrant inflammasome activation as a driving force of human autoimmune skin disease - Fetter, Tanja; de Graaf, Dennis Marinus; Claus, Isabelle; Wenzel, Joerg (Frontiers in Immunology, 2023)
Autoimmune skin diseases are understood as conditions in which the adaptive immune system with autoantigen-specific T cells and autoantibody-producing B cells reacting against self-tissues play a crucial pathogenetic role. However, there is increasing evidence that inflammasomes, which are large multiprotein complexes that were first described 20 years ago, contribute to autoimmune disease progression. The inflammasome and its contribution to the bioactivation of interleukins IL-1β and IL-18 play an essential role in combating foreign pathogens or tissue damage, but may also act as a pathogenic driver of myriad chronic inflammatory diseases when dysfunctionally regulated. Inflammasomes containing the NOD-like receptor family members NLRP1 and NLRP3 as well as the AIM2-like receptor family member AIM2 have been increasingly investigated in inflammatory skin conditions. In addition to autoinflammatory diseases, which are often associated with skin involvement, the inflammasome has also been described in autoimmune diseases that can either affect the skin besides other organs such as systemic lupus erythematosus and systemic sclerosis or are isolated to the skin in humans. The latter include, among others, the T-cell mediated disorders vitiligo, alopecia areata, lichen planus and cutaneous lupus erythematosus as well as the autoantibody-driven blistering skin disease bullous pemphigoid. Some diseases are characterized by both autoinflammatory and autoimmune responses such as the chronic inflammatory skin disease psoriasis. Further insights into inflammasome dysregulation and associated pathways as well as their role in forming adaptive immune responses in human autoimmune skin pathology could potentially offer a new field of therapeutic options in the future.